The Unique Heart Sound Signature of Children with Pulmonary Artery Hypertension. (1st December 2015) - Elgendi, Mohamed; Bobhate, Prashant; Jain, Shreepal; Guo, Long; Kumar, Shine; Rutledge, Jennifer; Coe, Yashu; Zemp, Roger; Schuurmans, Dale; Adatia, Ian
Abstract : We hypothesized that vibrations created by the pulmonary circulation would create sound like the vocal cords during speech and that subjects with pulmonary artery hypertension (PAH) might have a unique sound signature. We recorded heart sounds at the cardiac apex and the second left intercostal space (2LICS), using a digital stethoscope, from 27 subjects (12 males) with a median age of 7 years (range: 3 months–19 years) undergoing simultaneous cardiac catheterization. Thirteen subjects had mean pulmonary artery pressure (mPAp) < 25 mmHg (range: 8–24 mmHg). Fourteen subjects had mPAp ≥ 25 mmHg (range: 25–97 mmHg). We extracted the relative power of the frequency band, the entropy, and the energy of the sinusoid formants from the heart sounds. We applied linear discriminant analysis with leave‐one‐out cross validation to differentiate children with and without PAH. The significance of the results was determined with a t test and a rank‐sum test. The entropy of the first sinusoid formant contained within an optimized window length of 2 seconds of the heart sounds recorded at the 2LICS was significantly lower in subjects with mPAp ≥ 25 mmHg relative to subjects with mPAp < 25 mmHg, with a sensitivity of 93% and specificity of 92%. The reduced entropy of the first sinusoid formant of the heart sounds in children with PAH suggests the existence of an organized pattern. The analysis of this pattern revealed a unique sound signature, which could be applied to a noninvasive method to diagnose PAH.